Impact of Obesity Subtypes on Short-Term Weight Loss Following Vertical Sleeve Gastrectomy - Shah, Raj A.; Nath, Anand; Shope, Timothy R.; Lameda, Ivanesa L. Pardo; Brebbia, John S.; Koch, Timothy R. (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
Background: Temporal prevalence studies of worldwide obesity have confirmed that this epidemic continues to worsen and investigators have suggested that the scope of this problem may indeed be underestimated. The pathogenesis of the condition is multifactorial and complex, and it has been suggested that early life exposure to environmental chemicals (termed obesogens) may be a major cause of this epidemic. Aims: Vertical sleeve gastrectomy has become the most common surgical intervention for medically-complicated obesity. This study was designed to examine the distribution of clinical subtypes of obesity (e.g. psychosocial factors, genetic risk, or obesogens) and to identify the best candidates for vertical sleeve gastrectomy based on clinical subtype. Study Design: This is a retrospective cohort study in a large, urban teaching hospital. Place and Duration of Study: Center for Advanced Laparoscopic & Bariatric Surgery, MedStar Washington Hospital Center Washington, DC between October 2018 and June 2019. Methodology: Consecutive new individuals (n=225) with medically-complicated obesity were evaluated preoperatively in an outpatient bariatric gastroenterology clinic. Subjects (n=17) were excluded. Eighty-four individuals underwent sleeve gastrectomy with a minimum of 6 months of postoperative follow up. Results: Among the 3 subtypes, early life obesogen exposure was identified in 14.5% of individuals, genetic risk in 24.5% of individuals, and psychosocial factors in 61% of individuals. Percent excess weight loss (mean+/-SD) at 6 months is different among the three groups (pANOVA=.024). Individuals with genetic risk (38%+/-14) have significantly less weight loss (p=.029) than individuals with psychosocial factors (47%+/-15), while there is no difference compared to the obesogen subtype (41%+/-8.9). Conclusion: The most common clinical subtype of obesity is psychosocial factors, and there is significantly higher short-term weight loss after sleeve gastrectomy in individuals with psychosocial factors. It was also noted that individuals with genetic risk have significantly less weight loss than individuals with psychosocial factors, while there is no difference compared to the obesogen subtype. Weight loss may be moderated by an individual’s genetic risk and early life obesogen exposure.